THE MODERATION ROLE OF WORK RELATED SOCIAL SUPPORT IN JOB DEMAND RELATIONSHIPS WORK FAMILY CONFLICT AND FAMILY SATISFACTION - Irjuniawan P. Radjiman; Nuri Herachwati; Gebrina Ayu Nastiti; Gebrina Ayu Pramesti (Airlangga Development Journal, 2023)
Doctors are a profession that many people are interested in. However, most people don't understand that working as a doctor is not as easy as they imagine. Doctors are one of the jobs that have the highest level of stress compared to other jobs because other people's lives depend on their skills. Doctors must be ready whenever patients need them. Therefore, the aim of this research is to find out the role of moderation work related social support on relationships job demand work family conflict and family satisfaction. In this research, technique sampling which is used is nonprobability sampling. From the whole type in technique nonprobability sampling selected type purposive sampling which is in accordance with the research objectives. The sample in this study is a group that is believed to be able to provide the desired information, namely doctors who are married and have irregular working hours. The results of this research show that job demand provide a significant influence on work family conflict. work family conflict has an insignificant effect on family satisfaction.